2015
DOI: 10.1007/s11336-015-9482-9
|View full text |Cite
|
Sign up to set email alerts
|

A New Online Calibration Method for Multidimensional Computerized Adaptive Testing

Abstract: Multidimensional-Method A (M-Method A) has been proposed as an efficient and effective online calibration method for multidimensional computerized adaptive testing (MCAT) (Chen & Xin, Paper presented at the 78th Meeting of the Psychometric Society, Arnhem, The Netherlands, 2013). However, a key assumption of M-Method A is that it treats person parameter estimates as their true values, thus this method might yield erroneous item calibration when person parameter estimates contain non-ignorable measurement error… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 30 publications
3
50
0
Order By: Relevance
“…We found that MM‐MEM‐AMC significantly improved the calibration accuracy and efficiency compared to M‐MEM‐AMC. A possible reason is that the K nodes drawn from M‐OEM‐AMC are already accurate enough, and an inaccurate provisional estimate of Δjfalse(tfalse) brings more noise when updating N(boldθij|trueθ^ij(t+1),trueΩ^ij(t+1)) because M‐MEM often performs worse than M‐OEM especially for medium and large‐sized correlations between coordinate dimensions (Chen & Wang, ). Hence it is not worthwhile to keep drawing new sets of random nodes adaptively from the updated distribution N(boldθij|trueθ^ij(t+1),trueΩ^ij(t+1)), which obviously can be contaminated by the errors in Δjfalse(tfalse).…”
Section: Online Calibration Methods In Mcatmentioning
confidence: 99%
“…We found that MM‐MEM‐AMC significantly improved the calibration accuracy and efficiency compared to M‐MEM‐AMC. A possible reason is that the K nodes drawn from M‐OEM‐AMC are already accurate enough, and an inaccurate provisional estimate of Δjfalse(tfalse) brings more noise when updating N(boldθij|trueθ^ij(t+1),trueΩ^ij(t+1)) because M‐MEM often performs worse than M‐OEM especially for medium and large‐sized correlations between coordinate dimensions (Chen & Wang, ). Hence it is not worthwhile to keep drawing new sets of random nodes adaptively from the updated distribution N(boldθij|trueθ^ij(t+1),trueΩ^ij(t+1)), which obviously can be contaminated by the errors in Δjfalse(tfalse).…”
Section: Online Calibration Methods In Mcatmentioning
confidence: 99%
“…The number of examinees who answer each new item must be sufficiently large to provide accurate item parameter estimates without placing an undue burden on examinees (Wainer and Mislevy, 1990). This paper investigates one sample size (3,000) and assumes that each examinee answers 5 new items, thus the number of examinees who answer each new item is approximately 750 [(3,000×5)/20] on average as in previous studies (e.g., Chen et al, 2012;Chen and Wang, 2016;He et al, 2017). In Study 1, the number of examinees to each new item is set 700.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…where E(a r ) = exp(rm + (r 2 s 2 =2)) and F(Á) is the cumulative distribution function of standard normal distribution (P. Chen & Wang 2016;Lien, 1985). Thus, m a ¼ D E(aj0:2\a\2) = 0:8804 and var(a) ¼ D var(aj0:2\a\2) = 0:2296 can be obtained by setting L a = 0:2, U a = 2, m = 0, and s = 1.…”
Section: Generation Of Items and Examineesmentioning
confidence: 99%